Ethics of Pediatric and Young Adult Medical Decision-Making: Case-Based Discussions Exploring Consent, Capacity, and Surrogate Decision-Making - Jennifer deSante-Bertkau; Lori A. Herbst (Association of American Medical Colleges, 2021)
Introduction Most medical decisions in pediatrics involve surrogate decision-makers. Because of this, pediatricians are even more likely to encounter ethical conflicts and dilemmas surrounding medical decision-making. Pediatricians continue to report a lack of preparedness to manage situations when conflicts and dilemmas arise, suggesting a gap in education. In response to this gap, we developed a module on the ethics of medical decision-making focused on pediatrics. Methods The Ethics of Pediatric and Young Adult Medical Decision-Making module included three case-based, small-group sessions on decision-making capacity and advance directives, parental decision-making, and informed consent and adolescent assent. Session materials were developed based on expert opinion and previously published content. Sessions were developed for pediatric residents; however, medical students rotating on pediatrics also participated in most sessions. Trainees completed pre- and postsession assessments of comfort and understanding. Results An average of 19 learners completed each session. Understanding of ethical principles increased after each session. Seventy-nine percent of trainees reported increased understanding of ethical principles related to decision-making capacity, and 88% reported increased understanding of standards of surrogate decision-making. Following the session on obtaining consent and assent, 71% of trainees reported comfort obtaining consent compared to 57% reporting comfort obtaining assent. Discussion This module successfully increased trainee comfort with many ethical issues related to pediatric medical decision-making. Areas where trainee comfort was still low postsession-specifically, obtaining consent or assent-are content areas where actual practice of these psychomotor skills is likely necessary.